Digital business roadmap webinar: Exploring creative digital business idea - Artika Arista; Muhammad Eka Purbaya; Khairun Nisa Meiah Ngafidin (Community Empowerment, 2021)
In facing the industrial era 4.0, college graduates in information and computer science are required to adapt to the developments and needs of current industrial technology. The link and match between the world of education and industry is the key to optimizing the absorption of skilled labor. To answer these challenges, the Information systems undergraduate study program at Institut Teknologi Telkom Purwokerto, SUHU, and T-Lab held a Webinar Series "Link & Match of Information Technology between Academics and Industrial Needs" with the topic of Digital Business Roadmap: Exploring creative digital business ideas. This webinar activity is carried out using a mentoring method as well as sharing new knowledge with participants about Digital Business Transformation and how to explore creative digital business ideas. The result is that participants can understand digital business transformation and then explore creative digital business ideas to be developed in a business proposal.